Comparison of electrocoagulation and combined electrocoagulation-electrooxidation treatment for synthetic tannery wastewaters bearing phenolic syntan - Kumar, Amit; Basu, D. (Water, air, and soil pollution, 2024)
In this study, EC process using an aluminum anode, and EC-EO process using aluminum and mixed metal oxide, i.e., platinum-ruthenium dioxide-coated onto titanium (Al-Ti/Pt-RuO 2 ) anode was used to understand the remove of phenolic syntan (PS) from synthetic tannery wastewaters. The operational conditions of the abovementioned electrochemical processes were optimized using Taguchi L 16 method in terms of maximum removal of total organic carbon (TOC) and PS. At the optimum operating condition (current density = 14.25 mA/cm 2 , initial pH = 4, rotational speed = 70 rpm and initial PS amount = 0.25 g/L), the incomplete removal of TOC (83.93%) and PS (81.19%) was obtained in the EC process with the energy consumption of 0.135 kWh/g TOC remove and 0.056 kWh/g PS remove. In contrast, almost (≈100%) complete removal of the dissolved organic pollutant was observed in the EC-EO process with the energy consumption of 0.113 kWh/g TOC remove and 0.0453 kWh/g PS remove. The energy consumption per g TOC and PS removed was 0.135 and 0.056 kWh for the EC process, whereas 0.113 and 0.0453 kWh for the EC-EO process. The operating cost of the EC-EO process was estimated to be 1.39 USD/m 3 , which was lesser (-19.65%) than the operating cost of the EC process. Signal-to-noise ratio and ANOVA results showed that current density was the most influential parameter with the highest delta value and contribution ratio for TOC and PS removal in both the EC and EC-EO process. The UV/Vis and FT-IR analyses indicate that the highest removal of aromatic compounds was obtained in the EC-EO process compared to the EC process. FT-IR analyses confirmed that the PS was first degraded into a quinone functional group, which was further oxidized into carboxylic acid.